Floodplain management a new approach for a new era - Freitag, Bob (Island Press, 2009)
Outlines a paradigm for flood management, one that emphasizes cost-effective, long-term success by integrating physical, chemical, and biological systems with societal capabilities. This book describes flood management practices, which are often based on dam or levee projects that do not incorporate fresh understandings about river processes.